Exploring the link between Chinese household income and carbon emissions from 1994 to 2018: a partially closed input-output model approach - Chen, Hongqi; Kim, Man-Keun; Jiang, Weimin; Zhang, Yu (Frontiers in Environmental Science, 2025)
IntroductionExamining the impact of household income on carbon emissions is pivotal for linking the national strategy of common prosperity with the country's dual carbon goals.MethodsWe develop a partially closed input-output model differentiating urban and rural household income and consumption, and explore the impact of household income on carbon emissions.Results and discussionThe results show that from 1994 to 2018, the total carbon emissions induced by household income increased, while the carbon emissions per unit of household income decreased. In 2018, carbon emissions caused by household income accounted for 11.5% of China’s total carbon emissions (1,624 Mt). Among them, carbon emissions caused by household income in urban areas were 5.6 times that in rural areas. Apart from the energy sector, carbon emissions caused by household income are mainly concentrated in metal manufacturing, transportation, mining, agriculture, and food and tobacco industries, and carbon emissions show continuous growth trend. A comparison of open and partially closed input-output models shows that the open input-output model would over-estimate the carbon emissions caused by household income. This study provides important reference for the formulation of carbon emission reduction policies, the optimization of energy structures, and the balance between residents’ income growth and the achievement of dual carbon goals by region.